2019
DOI: 10.3390/ijerph16071120
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Association Between Depression and High-Risk Sexual Behavior Among Adult Latina Immigrant Farm Workers in Miami-Dade County

Abstract: Latinas are often more affected by HIV due to their socio-economic and demographic profiles and are also less likely to receive proper mental health care. Latina immigrants are often even more vulnerable due to socio-economic and cultural factors that place them at higher risk. The current study seeks to examine the association between depression and risky sexual behaviors among adult Latina immigrants from a farm working community in South Miami-Dade County, (Florida, USA). Cross-sectional secondary data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Research has identified the co-occurrence of different psychosocial problems, including poor mental health, substance use, self-stigma, violence, and social isolation, in HIV-vulnerable populations [19,20]. These psychosocial problems have been consistently found to be interrelated with one another, synergistically enhancing the risk of condomless sex and HIV infection among women [19], racial minorities [20], immigrant workers [21], transgender individuals [22], sex workers [23], and men who have sex with men (MSM) [17,24].…”
Section: Syndemic Theorymentioning
confidence: 99%
“…Research has identified the co-occurrence of different psychosocial problems, including poor mental health, substance use, self-stigma, violence, and social isolation, in HIV-vulnerable populations [19,20]. These psychosocial problems have been consistently found to be interrelated with one another, synergistically enhancing the risk of condomless sex and HIV infection among women [19], racial minorities [20], immigrant workers [21], transgender individuals [22], sex workers [23], and men who have sex with men (MSM) [17,24].…”
Section: Syndemic Theorymentioning
confidence: 99%
“…( Ettman et al, 2020 ) People with depression are more likely to be involved in behaviors that put them at risk for acquiring the human immunodeficiency virus (HIV), such as injection drug use or unprotected sexual encounters. ( Ahaneku et al, 2016 , Carney et al, 2019 , Marshall et al, 2013 , Kim et al, 2019 ) In this regard, it is believed that the prevalence of depression was highly correlated with HIV infection. ( Angelino, 2008 ) A previous study from a nationally representative survey demonstrated that around half of people with HIV screened positive for psychiatric disorders, including minor and major depression.…”
Section: Introductionmentioning
confidence: 99%